218k views
4 votes
Please explain this
(1+2i) (1-2i)

User Olathe
by
6.8k points

2 Answers

3 votes

(1+2i) · (1-2i) - Start with the given expression.

(1) · (1) · (1) · (-2i) + (2i) · (1) + (2i) · (-2i) - FOIL.

1 - 2i + 2i - 4i² - Multiply.

1 - 2i + 2i - 4 · (-1) - Replace i² with -1. - Note: i² = -1

1 - 2i + 2i + 4 - Multiply.

5 + 0i - Combine like terms.

5 - Simplify

So (1 + 2i) · (1-2i) = 5.

The expression is now in standard form a + bi where a =5 and b = 0

User Mohamed Saber
by
6.1k points
6 votes

Answer:

Explanation:

f: 1 * 1 = 1

o: 1 * - 2i

i: 2i * 1

l: 2i * - 2i = - 4i^2 = -4 * i^2 = -4 * -1 = 4

Answer

1 - 2i + 2i + 4

5

User Cbuchart
by
6.9k points